Tumor-targeted dose escalation for localized prostate cancer using MR-guided HDR brachytherapy (HDR) or integrated VMAT (IB-VMAT) boost: Dosimetry, toxicity and health related quality of life. (August 2020) - Sanmamed, Noelia; Lee, Jenny; Berlin, Alejandro; Craig, Tim; Lao, Bernadeth; Rink, Alexandra; Bayley, Andrew; Catton, Charles; Sundaramurthy, Aravindhan; Foltz, Warren; McPartlin, Andrew; Ghai, Sangeet; et al.
Highlights: Intraprostatic tumor dose escalation using IB-VMAT or MR-guided HDR boost is feasible. IB-VMAT and HDR boost achieve comparable dosimetry, toxicity and HRQOL outcomes. HDR boost achieved higher mean and maximal GTV doses than IB-VMAT. Abstract: Purpose: To report dosimetry, preliminary toxicity and health-related quality of life (HRQoL) outcomes of tumor-targeted dose-escalation delivered by integrated boost volumetric arc therapy (IB-VMAT) or MR-guided HDR brachytherapy (HDR) boost for prostate cancer. Materials and methods: Patients diagnosed with localized prostate cancer, with at least 1 identifiable intraprostatic lesion on multiparametric MRI (mpMRI) were enrolled in a prospective non-randomized phase II study. All patients received VMAT to the prostate alone (76 Gy in 38 fractions) plus a GTV boost: IB-VMAT (95 Gy in 38 fractions) or MR-guided HDR (10 Gy single fraction). GTV was delineated on mpMRI and deformably registered to planning CT scans. Comparative dosimetry using EQD2 assuming α/β 3 Gy was performed. Toxicity and health-related quality of life data (HRQoL) data were collected using CTCAE v.4.0, International Prostate Symptom Score (IPSS) and the Expanded Prostate Index Composite (EPIC). Results: Forty patients received IB-VMAT and 40 HDR boost. Organs at risk and target minimal doses were comparable between the two arms. HDR achieved higher mean and maximal tumor doses ( p  < 0.05). Median follow-up was 31 months (range 25–48); Acute grade G2 genitourinary (GU) toxicity was 30% and 37.5% in IB-VMAT and HDR boost, while gastrointestinal (GI) toxicity was 7.5% and 10%, respectively. Three patients developed acute G3 events, two GU toxicity (one IB-VMAT and one HDR boost) and one GI (IB-VMAT). Late G2 GU toxicity was 25% and 17.5% in the IB-VMAT and HDR boost arm and G2 GI was 5% and 7.5%, respectively. Two patients, both on the IB-VMAT arm, developed late G3 toxicity: one GI and one GU. No statistically significant difference was found in HRQoL between radiotherapy techniques ( p  > 0.2). Urinary and bowel HRQoL domains in both groups declined significantly by week 6 of treatment in both arms ( p  < 0.05) and recovered baseline scores at 6 months. Conclusion: Intraprostatic tumor dose escalation using IB-VMAT or MR-guided HDR boost achieved comparable OAR dosimetry, toxicity and HRQOL outcomes, but higher mean and maximal tumor dose were achieved with the HDR technique. Further follow-up will determine long-term outcomes including disease control.